Psychological Mechanisms Involved in Radicalization and Extremism. A Rational Emotive Behavioral Conceptualization - Trip, Simona; Bora, Carmen Hortensia; Marian, Mihai; Halmajan, Angelica; Drugas, Marius Ioan (Frontiers in Psychology, 2019)
Extremist acts and the process of radicalizations got into researchers’ attention worldwide since 2001. The aim of this paper is to offer a broad image on radicalization and extremist acts and to bring a new perspective for the conceptualization of radicalization. Radicalization is a process of developing extremist beliefs, emotions and behaviors. The beliefs are zeal, profound convictions opposite to what means fundamental values of society, laws of democracy and universal human rights, by advocating the supremacy of a certain group (racial, religious, political, economic, social etc.). The extremist emotions and behaviors may be expressed both in non-violent pressure and coercion and in actions that deviates from the norm and show contempt for life, freedom and human rights. A complete inroad to psychological mechanism involved in the process ofradicalization is offered in order to have a broad image regarding current research in the field. Starting from this point a rational emotive and behavioral conceptualization on radicalization have been developed bringing together all the concepts and knowledge in the field. A complete and clear conceptualization is crucial for developing prevention/intervention programs and good practices in dealing with this process which is spreading in the past years. The final part deals with directions regarding prevention/intervention programs form a rational emotive and behavioral perspective, but also from the perspective of European policies.